Acute Injuries in Track and Field Athletes: A 3-Year Observational Study at the Penn Relays Carnival With Epidemiology and Medical Coverage Implications. (April 2015) - Opar, David; Drezner, Jonathan; Shield, Anthony; Williams, Morgan; Webner, David; Sennett, Brian; Kapur, Rahul; Cohen, Marc; Ulager, James; Cafengiu, Anna; Cronholm, Peter F.
Background: Few studies have examined acute injuries in track and field in both elite and subelite athletes. Purpose: To observe the absolute number and relative rates of injury in track and field athletes across a wide range of competition levels and ages during 3 years of the Penn Relays Carnival to assist with future medical coverage planning and injury prevention strategies. Study Design: Descriptive epidemiology study. Methods: Over a 3-year period, all injuries treated by the medical staff were recorded on a standardized injury report form. Absolute number of injuries and relative injury rates (number of injuries per 1000 competing athletes) were determined and odds ratios (ORs) of injury rates were calculated between sexes, competition levels, and events. Injuries were also broken down into major or minor medical or orthopaedic injuries. Results: Throughout the study period, 48, 473 competing athletes participated in the Penn Relays Carnival, and 436 injuries were sustained. For medical coverage purposes, the relative rate of injury subtypes was greatest for minor orthopaedic injuries (5.71 injuries per 1000 participants), followed by minor medical injuries (3.42 injuries per 1000 participants), major medical injuries (0.69 injuries per 1000 participants), and major orthopaedic injuries (0.18 injuries per 1000 participants). College/elite athletes displayed the lowest relative injury rate (7.99 injuries per 1000 participants), which was significantly less than that of high school (9.87 injuries per 1000 participants) and masters athletes (16.33 injuries per 1000 participants). Male athletes displayed a greater likelihood of having a minor orthopaedic injury compared with female athletes (OR, 1.36 [95% CI, 1.06-1.75]; χ 2 = 5.73; P = .017) but were less likely to sustain a major medical injury (OR, 0.33 [95% CI, 0.15-0.75]; χ 2 = 7.75; P = .005). Of the 3 most heavily participated in events, the 4 × 400-m relay displayed the greatest relative injury rate (13.6 injuries per 1000 participants) compared with the 4 × 100-m and 4 × 200-m relays. Conclusion: Medical coverage teams for future large-scale track and field events need to plan for at least 2 major orthopaedic and 7 major medical injuries per 10, 000 participants. Male track and field athletes, particularly masters male athletes, are at greater risk of injury compared with other sexes and competition levels.